Corporate Mission Statements: An Appraisal-Based Study - Alsagri, Weaam Abdullah (International Journal of Language and Literary Studies, 2024)
A corporate mission statement aims to communicate the established goals of a company internally and externally. In this type of statement, attitude plays an important role in the expression of interpersonal linguistic meanings. Therefore, following Martin and Rose’s (2007) systemic functional linguistics (SFL) approach, this paper qualitatively analyzed the mission statements of the companies that hold the top seven spots in Fortune’s corporate reputation rankings in 2021, namely Apple, Amazon, Microsoft, Walt Disney, Starbucks, Berkshire Hathaway, and Alphabet, from the perspective of the appraisal system. The results indicate that the most common sub-system of attitude found in these corporate mission statements was positive appreciation. However, it was also found that the distribution patterns of evaluation resource words of the selected mission statements are not quite similar. Further, given the functions of this particular genre, that is, shaping the identity of the company and its employees, it was found that the selected corporate mission statements employ attitudinal resources that are all positive in orientation.